(untitled) (Research, Society and Development, 2022)
This work aims to understand the functioning of Human Resources Management in the Public Sector. The methodology used was bibliographic research. Public administration’s main objective is to meet the public interest and social needs. For the fulfillment of its administrative function, the State has certain prerogatives guaranteed by law; however, such prerogatives need to be used in the fulfillment of the actions that were proposed in its creation. In public administration, managing goes beyond performing public services, but directing and managing seeking the good and satisfaction of society. The literature on people management in the private area is quite extensive, however, that specific to the public area is scarce and dispersed. For a long time, people management in the public area had as its main focus the performance of operational activities, with no clear instructions on the guidelines that governed human resources. The lack of training and team participation were lost due to the lack of objectives, as the level of commitment that requires change is high, where they are often not seen as improvement, but a waste of time.